Secondary Seizures in the Pediatric Population in Two Tertiary Hospitals in India - Kumar, Arun; Marimuthu, Thangaraj; Kannan, Lakshminarayanan; Agarwal, Vikash; Nayak, Dinesh (International Journal of Integrated Health Sciences, 2023)
Objective: To evaluate the clinical pattern of secondary seizures which includes acute and remote symptomatic seizures among hospitalized patients in two healthcare centers and to assess the outcomes among hospitalized patients having secondary seizures.Methods: This multicentric cross-sectional study was conducted in two tertiary hospitals in Odisha and Tamil Nadu, India, for a period of four years. A total of 274 patients in the age group between 6 months to 12 years participated in the study. A structured proforma was used to document the clinical pattern and causes of the secondary seizures.Results: Among the participants in Odisha and Tamil Nadu hospitals, focal seizures constituted 67.5%. Generalized seizures were present in 32.4%. The key causes of seizures in Odisha were malaria, cerebral palsy, and viral meningitis, while in Tamil Nadu, the causes were neurocysticercosis, cerebral palsy, and viral meningitis.Conclusion: Since the majority of the causes are preventable, it is important to address the issue at the public health level, by providing improved sanitation and adequate awareness on the secondary seizure and its causes. It is also important that the physicians are well conversant with the early case detection and treatment of primary diseases causing secondary seizures.